Brain uptake and safety of Flutemetamol F 18 injection in Japanese subjects with probable Alzheimer’s disease, subjects with amnestic mild cognitive impairment and healthy volunteers - Miki, Takami; Shimada, Hiroyuki; Kim, Jae-Seung; Yamamoto, Yasuji; Sugino, Masakazu; Kowa, Hisatomo; Heurling, Kerstin; Zanette, Michelle; Sherwin, Paul F.; Senda, Michio (Annals of nuclear medicine, 2017)
Objective This Phase 2 study assessed the performance of positron emission tomography (PET) brain images made with Flutemetamol F 18 Injection in detecting β-amyloid neuritic plaques in Japanese subjects. Methods Seventy subjects (25 with probable Alzheimer’s disease (pAD), 20 with amnestic mild cognitive impairment (aMCI), and 25 cognitively normal healthy volunteers[HVs]) underwent PET brain imaging after intravenous Flutemetamol F 18 Injection (185 MBq). Images were interpreted as normal or abnormal for neuritic plaque density by each of five non-Japanese and five Japanese readers who were blinded to clinical data. The primary efficacy analysis (based on HV and pAD data) was the agreement of the non-Japanese readers’ image interpretations with the clinical diagnosis, resulting in estimates of positive percent agreement (PPA; based on AD subjects; similar to sensitivity) and negative percent agreement (NPA; based on HVs; similar to specificity). Secondary analyses included PPA and NPA for the Japanese readers; inter-reader agreement (IRA); intra-reader reproducibility (IRR); quantitative image interpretations (standardized uptake value ratios [SUVRs]) by diagnostic subgroup; test–retest variability in five pAD subjects; and safety. Results PPA was 92% for all non-Japanese readers and ranged from 88 to 92% for the Japanese readers. NPA ranged from 96 to 100% for both the non-Japanese readers and the Japanese readers. The majority image interpretations (the interpretations made independently by ≥3 of 5 readers) resulted in PPA values of 92 and 92% and NPA values of 100 and 96% for the non-Japanese and Japanese readers, respectively. IRA and IRR were strong. Composite SUVR values (mean of multiple regional values) allowed clear differentiation between pAD subjects and HVs. Test–retest variability ranged from 1.14 to 2.27%, and test–retest agreement of the blinded visual interpretations was 100% for all readers. Flutemetamol F 18 Injection was generally well tolerated. Conclusions The detection of brain neuritic plaques in Japanese subjects using [ 18 F]Flutemetamol PET images gave results highly consistent with clinical diagnosis, with non-Japanese and Japanese readers giving similar results. Inter-reader agreement and intra-reader reproducibility were high for both sets of readers. Visual delineation of abnormal and normal scans was corroborated by quantitative assessment, with low test–retest variability. Trial registration Clinicaltrials.gov registration number NCT02813070.